Biogeneic Treatment for Crack Remediation and Self-Healing in Concrete Structures - Shelly, Chauhan (My University, 2022)
Concrete is the most widely and extensively used material. Due to easy susceptibility of concrete to crack formation, it has become a challenge to protect concrete from pre-mature damage. It is a great task to identify microcracks at an early stage and then to cure them before they increase in size. Apart from using conventional techniques used for repair and maintenance of cracks this study focusses on using microbial based self-healing for curing and sealing cracks. For remediation in cracks, precipitation of calcium carbonate is one of the best- known techniques. The technique is not only used for healing the crack but improve durability and mechanical strength of concrete samples. The environmental changes e.g., fluctuations in temperature and pH can lead to hinderance in production of calcium carbonate produced by MICCP. These environmental factors directly affect the metabolism of bacteria in calcium carbonate production. Due to exposure of bacteria to such harsh environmental conditions MICCP could not take place effectively. This effects the viability of bacteria and its ability to of hydrolysing urea. So, to thrive through such environmental conditions the bacterial spores of Bacillus paramycoides were used instead of bacterial vegetative cells. In order to safe-guard bacteria inside high alkaline cementitious environment hydrogel was made. Hydrogel was used as the carrier material for immobilizing spores and then incorporating it to crack. Hydrogel properties were studied when it was exposed to unfavourable conditions. The study highly emphasizes on bacterial based self-healing approach for enhancing effectiveness of building materials. In order to achieve the aim of the study at best the potential of bacterial spores encapsulated in hydrogel has been explored.
M.Sc thesis
Keywords: MICCP; Biomineralization; Hydrogel; Self- Healing; Swelling Kinetics; Sem